Hyperconnectivity of prefrontal cortex to amygdala projections in a mouse model of macrocephaly/autism syndrome - Wen-Chin Huang; Youjun Chen; Damon T. Page (Nature Communications, 2016)
Dysregulation of mTOR signaling has been implicated in autism spectrum disorders. Here authors show that hyperconnectivity and hyperactivity of the mPFC–BLA circuitry inPten+/−mice underlies their social impairments, and that reducing mTORC1 signaling during early postnatal development rescues these deficits.